‘Unborn’ and ‘indestructible’ as signs of truth in Parmenides in the context of the notion of time - Biedrzyński, Dawid Wojciech (Folia Philosophica, 2018)
Parmenides in his revolt of the first philosophy discarded the principle — arche and introduced in its place being — to eon. The effectivess of this revoltion of thought rested upon — among others — revealing a permanent connection between logic and ontology which connection was most seen in ‘signs of truth’, i.e. features of being. Two of these features — ‘unborn’ and ‘indesrtructible’ — show in a sense entanglement in the context of time whose consideration requires the analysis of Parmenides’ poem and insight into historical-philosophical development of the notion of time from the perspective of its use by natural philosophers in defining the principle — arche.